Conceptual Study of Local Wisdom-Based Education Management Strategy in the 3T (Disadvantaged, Frontier, and Outermost) Areas of Simeulue Regency (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study aimed to examine educational management strategies based on local wisdom in disadvantaged, frontier, and outermost (3T) areas, particularly in Simeulue Regency. The main focus is on how local values can be systematically integrated into education management to improve the quality and relevance of education in remote areas. Methods: This study used a qualitative approach based on conceptual literature studies. Data were collected through a search of scientific literature, government policies, and previous research results relevant to the topic of local wisdom and education management in the 3T region. The analysis was carried out descriptively and critically to compile a synthesis of education management models based on local cultural values. Results: The results of the study show that education in 3T areas faces infrastructure constraints, limited teachers, and low community participation. However, there is great potential in local wisdom, such as smong culture, mutual cooperation, and nandong, that can be integrated into the education management system. The synthesis produced a conceptual model based on participation, local values, and curriculum contextualization. Novelty: The novelty of this study lies in the systematic mapping of local values particularly smong and nandong into a coherent strategic management framework that transforms cultural wisdom into an operational education model. This conceptual contribution provides a new perspective on how indigenous cultural systems can be institutionalized within educational management structures, offering theoretical and practical implications for sustainable education in 3T regions.